Child Care in the United States: Markets, Policy, and Evidence - Chris M. Herbst (Institute of Labor Economics (IZA), 2022)
Participation in non-parental child care arrangements is now the norm for preschool-age children in the U.S. However, child care services are becoming increasingly expensive for many families, and quality is highly uneven across providers and sectors, raising questions about the impact of child care costs and quality on parental employment and child development. The U.S. policy landscape is dominated by three policies that subsidize costs for low-income families or attempt to improve the safety and quality of providers: Child Care and Development Fund, regulations, and quality rating and improvement systems. In this paper, I provide a thorough review of the evidence on each policy, focusing on how they influence a wide range of family and provider outcomes. The paper begins with a detailed description of the structure and functioning of the child care market, using the most up-to-date data on families' utilization of care services and provider characteristics. I then draw on a diverse set of studies across multiple fields to summarize the evidence on the impact of child care policy. In the final section of the paper, I offer recommendations for future research in each policy area.
Keywords: H75; I24; I38; J24; 330; child care; subsidies; regulations; maternal employment; child development